PENGARUH MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI THINK-TALK-WRITE DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MENULIS NASKAH DRAMA SISWA KELAS VIII SMP NEGERI 3 BATANG ANAI - Bunga .; Harris Effendi Thahar; Novia Juita (Fakultas Bahasa dan Seni UNP, 2014)
Abstrack: This study aimed to clarify the effect of the model cooperatif learning strategies Think-Talk-Write and high motivation and low motivation to learn the study to write a drama students class VIII SMP Negeri 3 Batang Anai. The population was class VIII SMP Negeri 3 Batang Anai. Sampling totaled 63 students conducted by purposive sampling. Data collected through questionnaires and tests. Questionnaire used to see students' motivation and performance tests conducted to determine the result of study to write a drama of students. Analysis and discussion of the data is done in accordance with the descriptive-analytical study concept experiments. Based on the results of the data analysis we can conclude the following four things. First, the result of study to write a drama that taught using model cooperative learning strategies Think-Talk-Write better than students taught by conventional methods. Second, there is no interaction between learning motivation and learning methods in affecting student’ result of study to write drama. Third, the result of study to write a drama of students who have high motivation are taught using model cooperative learning strategies Think-Talk-Write better than that taught by convensional methods. Fourth, the result of study to write a drama of students who have low motivation are taught using model cooperative learning strategies Think-Talk-Write better than that taught by convensional method. Keywords: cooperative learning, strategies Think-Talk-Write, learning and motivation, a drama writing